A Randomized Controlled Trial Evaluating the Impact of Dietary Supplementation with Polyphenols on Disease Severity and Quality of Life in Adults with Moderate to Severe Atopic Dermatitis in Beijing, China - Zhou, Suyong; Jinfang Zhang (Phlox Institute: Indonesian Medical Research Organization, 2023)
Introduction: Atopic dermatitis (AD) is a chronic inflammatory skin condition that significantly affects quality of life. Polyphenols, with their anti-inflammatory and antioxidant properties, offer a potential therapeutic avenue for AD management. Methods: This randomized, double-blind, placebo-controlled trial enrolled adults with moderate to severe AD in Beijing. Participants were randomized to receive either a polyphenol-rich dietary supplement or a placebo for 12 weeks. The primary outcome was the change in Scoring Atopic Dermatitis (SCORAD) index. Secondary outcomes included quality of life assessment using the Dermatology Life Quality Index (DLQI), and serum inflammatory markers. Results: A total of 120 participants completed the trial. The polyphenol group showed a significantly greater reduction in SCORAD index compared to the placebo group (p < 0.001). DLQI scores also improved significantly in the polyphenol group (p < 0.01). Furthermore, serum levels of inflammatory markers, including C-reactive protein and interleukin-6, decreased significantly in the polyphenol group. Conclusion: Dietary supplementation with polyphenols may offer a safe and effective adjunctive therapy for improving disease severity and quality of life in adults with moderate to severe AD.